Experiences in affective-sexual obesity contexts - Pereira, Filomena (2017)
The adverse effects of obesity are well documented; however, a growing topic is that relationship between obesity and sexuality. Studies show association between obesity and a decrease in sexual desire and involvement, avoidance of sexual encounters, difficulties in sexual performance, reduced number of sexual partners, and more than the male, females to report poor quality of sexual life. Objective: Recognize statistical relationships between the level of Body Mass Index (BMI) and sexual experiences. (number of sexual partners and frequency of sexual relations) Methodology: We proceeded to a quantitative descriptive methodology through the BMI calculation to a sample of 306 users of Obesity Therapy (30.7% gender male and 69.3% female) aged 18 and 65 years and a questionnaire to describe the participants with sexual experiences. Results: Respondents with higher BMI have lower qualifications. As the sample states, regarding the number of sexual partners, it appears that higher the BMI the lower number of sexual partners. Individuals with normal weight and pre-obesity present frequency of sexual relations / week between 2/3 times / week, while individuals with Obesity Grade II and Grade III have this frequency 1/2 times/week. Conclusion: BMI assumes influence of variable outlines the quality of affective and sexual experiences. It is considered urgent and relevant to invest in Sexual Education and Nutrition at the level of these populations.